Coconut Dehusking Machine - Istas Fahrurrazi, Muhammad Faisal Adha bin Istas Fahrurrazi; bin Mohd Nasir, Muhammad Amir Aqmar; bin Kamal, Abdul Aziz; binti Mohammad Noor, Hafsa (Multidisciplinary Applied Research and Innovation, 2022)
In Malaysia, coconut dehusking is one of the most important jobs to do since the domestic use of the product varies, mainly to produce coconut milk. Currently, there are many designs of the coconut dehusking machine available in the market right now, ranging from simple, old-school peeling device to electrical shredder machines. The problem with the current designs is the cost of operating it since it requires electricity, safety problems and consume high labour energy. The Coconut Dehusking Machine is designed to solve these problems. To put it simple, the machine is split into three operations, piercing, peeling and shearing operation. The piercing operation is when the ram is pushed the top moving blade, top static blade and bottom static blade pierces the coconut husk. After that, in the peeling operation, the ram is depressed further until the top moving blade is pushed radially outwards. The bottom blade holder is then rotated using a bottom lever to apply shear force on the husk to remove it from the shell. This design is much more portable since there are wheels installed on the base of the machine. The blades in this design also accommodates the type of coconut used in Malaysia. In this report, the model of the coconut dehusking machine will be fabricated to demonstrate the use of the coconut dehusking machine. It can be concluded that the fabrication of this model fulfil the study objectives. Although, there are a few improvements such as modifying the height of the blade so that more peeling force can be applied to the husk.